Understanding the students’ expectations in advisor in thesis supervision: case study of MKT672 - Mohammad, Noorita; Md. Dahlan, Jaslin; Ahmad, Haryati (2014)
The role of thesis supervision is to encourage students to develop sound research skills, to advance and create knowledge and become critical thinkers in their chosen fields of study, and to conduct enquiries in their areas of specialization in a professional, expert and ethical manner. Thesis quality and acquired experiences are highly dependent on their advisors. This paper investigated the expectations of the final-year students towards their thesis supervisors in writing their thesis and how thesis advisors can help the students to meet with their expectations. The data were collected using focus groups interviews with ten final year undergraduate students of UiTM Johor. The results of the research discovered that the students want to be independent and able to show their research skill at the initial stage of the research stage, with the guidance and continuous advice from their advisors. However, they need more assistance in the later stages; checking grammar and deciding on the methodologies; ensuring that they submit on time and monitoring their progress. It is hoped that this results of this paper will enable academic managers to create new curricular and programs in assisting both students and advisors on the effective thesis supervision.